Strategi Perpustakaan terhadap Peningkatan Minat Baca dan Budaya Baca Siswa di Perpustakaan SMA Negeri 2 Sukoharjo - Salsabila Ifany Sari, Clarissa; Arifin, Zainal (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 23 No 1 (2023), 2023)
The face of a nation can be seen from the face of its library and a nation's level of progress can be seen from the level of interest in reading. Directly or indirectly reading habit is an indicator of school quality and even nationally determines the high and low of the human development index (HDI) and the high or low of HDI which determines the quality of a nation. Based on the description above, the formulation of the problem in this research is as follows: 1) How is the library's strategy towards increasing students' reading culture in the SMA Negeri 2 Sukoharjo library?, 2) What are the obstacles that occur in the library's strategy towards increasing students' reading culture in the SMA Negeri 2 library? Sukoharjo?. The author suggests the following conclusions: 1) The library's strategy in increasing visitor interest in terms of user service aspects focuses on reliability, responsiveness, quality assurance of service, and a sense of empathy for users. 2) Library strategy in increasing visitor interest in terms of facilities and infrastructure: a) Placement of library rooms that are strategic and easily accessible by users b) Arrangement of shelves (bookcases, tables, reading chairs) strategic and orderly c) Provide collections (collections general books, references, journals) complete according to the needs of users. d) Provide complete and adequate facilities (bookcases, magazine racks, drawing cabinets, cabinets or catalog cabinets, bulletin boards, reading tables, chairs, display boards, OPAC). e) Providing an internet network that supports users to access information.